The synthesis, reactivity and the antimicrobial activity of substituted thieno[2,3-d]pyrimidine- 4(3H)-thio(seleno)nes - Kolomieitsev, D. O.; Markov, V. I.; Astakhina, V. O.; Kovalenko, S. I.; Varenichenko, S. A.; Kharchenko, O. V.; Коваленко, Сергій Іванович (НФаУ, 2015)
A new series of R1,R2-thieno[2,3-d]pyrimidine-4(3H)-one, thione and selenone derivatives have been synthesized; the reaction of alkylation of the compounds obtained has been studied. Their structures have been confrmed by the NMR 1H and mass spectra, and elemental analysis. The antibacterial and antifungal activities in vitro against three bacterial and two fungal pathogens have been revealed using the stiff plate agar diffusion method and the serial dilution method. The minimal bactericidal, fungicidal and bacteriostatic concentrations have been obtained. The pharmacological screening has shown that some of the compounds obtained possess a good antimicrobial activity. The culture of S.aureus. appeared to be the most sensitive to compound 10a. The best fungistatic indicators against A.niger have been found for compounds 4a and 9a.
Синтез, реакційна здатність та антимікробна активність заміщених тієно[2,3-d]піримідин-4(3Н)-тіо(селено)нів
Keywords: thieno[2,3-d]pyrimidine-4(3H)-thio(seleno)nes; alkylation; antibacterial activity